Can agricultural insurance play a protective role? Evidence from China’s agriculture - Wensheng Wang; Yehong Zhong (Humanities & Social Sciences Communications)
Abstract Agricultural insurance plays a critical role in promoting the agricultural economy. However, the precise influence of agricultural insurance on diverse facets of agricultural economy development remains under explored. This study empirically analyses the effects of agricultural insurance on agricultural economy development by applying the two-way fixed effects model, the heterogeneity test model, and the mediation effect model using China’s provincial-level agricultural economic data from 2004 to 2021. The results reveal that agricultural insurance has a positive impact on the development of agricultural economy, with every one-unit increase in the contribution level of agricultural insurance leading to an 8.99% enhancement in the level of the agricultural economy. Heterogeneity tests show that agricultural insurance can better protect and promote the agricultural economy in the eastern regions, non-major grain-producing areas, and during periods of low natural disaster impact. Mechanism analysis reveals the mediating effects of agricultural production inputs, agricultural production and operation scale, and mechanization in promoting agricultural economic development through agricultural insurance. The findings of this study hold policy significance for improving agricultural insurance system, promoting rural revitalization, and protecting the development of the agricultural economy.